Compensation Management studies: A Review (International Journal of Food and Nutritional Sciences, 2023)
This research illuminates the strategic dimensions of Compensation Management, unraveling its profoundinfluence on organizational success and workforce dynamics. As the global workplace undergoestransformative shifts, the need to navigate the intricacies of employee rewards becomes paramount. Thisone-page abstract encapsulates the essence of a comprehensive exploration, offering a valuable resource forHR professionals, business leaders, and scholars aiming to enhance their understanding and implementationof strategic Compensation Management practices